2003
DOI: 10.1111/1541-1338.00029
|View full text |Cite
|
Sign up to set email alerts
|

Equal Employment Policy in France: Symbolic Support and a Mixed Record

Abstract: This article analyzes the policy framework for and the implementation of equal employment policy in France. After presenting the equal employment policy framework and the role of state feminist womenS policy offices in its development, the author discusses the limited support for positive action strategies among French firms and unions. The implementation of equal employment policy has had a mixed record, often limited to symbolic gestures rather than concrete change. Contributing to this symbolic dynamic are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…Indeed, the best of policies oriented toward gender equity work to ensure that men are truly involved in caregiving, as in "daddy days" of leave that only men can take; recent research suggests that the take-up of such policies is growing. For example, the fairly short French paid paternity leave adopted in 2002 has been tremendously successful; 94 percent of fathers take the leave for the maximum period (Laufer 2003;Mazur 2003). However, the leave should be longer to truly engage men in caretakingcurrently, it is available for only 11 days within the first four months of a baby's birth or adoption or 18 days within the first four months of the birth or adoption of multiple babies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the best of policies oriented toward gender equity work to ensure that men are truly involved in caregiving, as in "daddy days" of leave that only men can take; recent research suggests that the take-up of such policies is growing. For example, the fairly short French paid paternity leave adopted in 2002 has been tremendously successful; 94 percent of fathers take the leave for the maximum period (Laufer 2003;Mazur 2003). However, the leave should be longer to truly engage men in caretakingcurrently, it is available for only 11 days within the first four months of a baby's birth or adoption or 18 days within the first four months of the birth or adoption of multiple babies.…”
Section: Discussionmentioning
confidence: 99%
“…French women, for example, have access to expansive stateprovided child care, generous parental leave, and home care allowances that support parental care for two or more young children. French policies are promoted as giving women a "free choice" (libre choix) (Laufer 2003;Morgan 2004Morgan , 2005. While the provision of child care supports relatively high employment levels for mothers, as a whole, these policies have encouraged women's caregiving rather than promoted men's equal role in care (Morgan 2004(Morgan , 2005.…”
Section: Gendered Welfare State Strategiesmentioning
confidence: 99%
“…Each year, the company's Works Council must issue an opinion on this gender equality reporting. Despite having been described as symbolic, because the concrete implementation of these duties was not included (Laufer, ; Mazur, ), this law put the principle of numerical measurement at the centre of equality bargaining. It nevertheless rested on the optimistic belief that the simple fact of calculating inequalities would trigger actions that could solve them.…”
Section: Quantification and Equal Employment Policies In France: An Omentioning
confidence: 99%
“…Particularly noteworthy here is the fact that French law effectively prevents AA programs. While some declare that efforts to establish equality in employment opportunities in France have been rendered ineffective due to the legal system in France, others complain about the failed integration model in French society (see article in New Statesman , 2005; Laufer, 2003). President Sarkozy, before his ascent to the presidency, suggested that France should abandon the pretence that all its citizens – including an estimated five million Muslims, many of African origin – are treated equally, and adopt AA policies (as in Canada and Ireland).…”
Section: Overview Of Ee Legislation In Canada France and Irelandmentioning
confidence: 99%